(untitled) (Journal of Paediatric Surgeons of Bangladesh, 2026)
Background: Stoma reversal, which involves restoring intestinal continuity, is a complex but commonly performed elective procedure in pediatric surgery. However, it carries significant risks, including postoperative complications and even mortality. This study aimed to evaluate early postoperative complications associated with hand-sewn modified double-layer intestinal anastomosis following stoma reversal in children who had previously undergone definitive bowel surgery. Methods: This retrospective study was conducted in the Department of Pediatric Surgery at Chattogram Maa-O-Shishu Hospital Medical College over a period of eleven years, from January 2014 to December 2024. A total of 673 children who underwent stoma closure were included in this study. We analyzed the indications for stoma formation, the duration from creation to closure of the stoma, operative time, and length of hospital stay. Early postoperative complications were assessed using the Clavien-Dindo classification within the first 30 days after surgery. Patients were followed up at two and four weeks after the procedure. Results: The median age of the participants was 2.17 ± 0.8 years (IQR: 1.4 - 4.5 years), with a male-to-female ratio of 2.17:1. The primary indications for the initial surgery, which involved stoma formation, included anorectal malformation (231 cases), Hirschsprung’s disease (183 cases), intussusception (110 cases), jejunoileal atresia (53 cases), meconium ileus (22 cases), pelvic or blunt abdominal trauma (22 cases), postoperative bands and adhesions (18 cases), ileocecal tuberculosis (12 cases), lymphoma (7 cases), Meckel’s diverticulum with bands (11 cases), and typhoid ulcer perforation (4 cases). The median interval between the primary procedure and stoma closure was 62 weeks (IQR: 48–76 weeks). The median operative time was 108 minutes. A total of 219 patients (32.5%) experienced postoperative complications, which included surgical site infection (SSI) (37.8%), anastomotic leak (15.1%), small bowel obstruction or paralytic ileus (9.6%), post-operative diarrhea (8.2%), enterocutaneous fistula (4.2%), gastrointestinal bleeding (3.2%), and postoperative intra-abdominal abscess (2.3%). Medical complications accounted for 19.7% of all complications, with pneumonia (12.3%) being the most common. Reoperations were required due to intestinal obstruction, anastomotic leak, and post-operative intra-abdominal abscess. Additionally, 57 associated procedures were performed, including 13 appendectomies, seven inguinal herniotomies, and 37 circumcisions. Twenty-three patients required a stay in the Pediatric Intensive Care Unit (PICU) following reversal surgery, and seventeen of these patients survived successfully. The median length of hospital stay for these patients was 8.4 days, ranging from 7.3 to 12.1 days. Conclusions: There were several indications for stoma formation in children. Surgical site infections (SSIs) were the most common complication following stoma reversal. While most complications could be managed conservatively, cases of anastomotic leak and intestinal obstruction necessitated reoperation. Journal of Paediatric Surgeons of Bangladesh (2022) Vol. 13 (1 & 2): 36-43